10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
The concept of the obsessive-compulsive spectrum has exerted a major influence on contemporary psychiatry and contributed substantially to the establishment of the DSM-5 category of obsessive-compulsive and related disorders. However, the notion of obsessionality employed within this framework does not necessarily correspond to the classical psychopathological concept developed in European descriptive psychopathology. This paper reexamines the concept of obsessionality through a psychopathological comparison with neighboring phenomena, including impulsivity, addiction, autochthonous thinking, stereotypy, tic disorders, and motoric forms of obsessive-compulsive disorder (OCD). Classical descriptions by Kraepelin, Jaspers, Schneider, and others suggest that obsessionality is characterized not merely by repetitive thoughts or behaviors, but by a distinctive cognitive structure involving compelling force, accompanying anxiety, awareness of irrationality, and an ego-dystonic yet self-attributed experience. Many conditions currently incorporated into the obsessive-compulsive spectrum, particularly motoric OCD and related repetitive behaviors, appear to differ fundamentally from classical obsessionality and may be more closely related to impulsive, addictive, neurological, or developmental phenomena. To accommodate these diverse conditions, this paper proposes the provisional category of "middle-voiced repetitive phenomena," encompassing repetitive thoughts and behaviors that are neither fully voluntary nor wholly passive. We argue that the expansion of the obsessive-compulsive spectrum has obscured the distinctive cognitive features that historically defined obsessionality. Returning to the classical psychopathological definition may therefore be useful for both clinical practice and research.